Intraocular Lens (IOL) Exchange Procedure in Refractive Surprise After Ten Years of Cataract Surgery - Audina, Rizna; Zahrah, Alvi Laili; Dharmawidiarini, Dini; Napitupulu, Sahata P. H. (Universitas Airlangga, 2024)
Introduction: Postoperative refractive surprises may manifest following cataract surgery. A residual refraction difference of > 2.0 D after cataract surgery was considered a refractive surprise. Treating refractive error after cataract surgery includes non-surgical and surgical options. The objective is to report clinical outcomes of intraocular lens (IOL) exchange with ciliary sulcus placement technique to manage refractive surprise. Case Presentation: A female patient aged 70 years reported experiencing blurred vision in her right eye (RE) for the past two years. History of RE cataract surgery ten years ago, however, she only had control 1-2 times after surgery. After that, the patient underwent cataract surgery on the left eye (LE), and then she complained that her RE was getting blurry. Her RE's visual acuity (VA) was 1/60 with best corrected visual acuity (BCVA) S-8.00 C-1.00 X100° to 6/10, and her LE was 7/10 with BCVA C-0.75 X60° to 10/10. The anterior segment examination of the RE was a 3-piece sulcus intraocular lens with complete continuous curvilinear capsulorhexis (CCC) intact anterior capsule, posterior capsule rupture, and the LE was in the bag IOL. Ultrasound examination of the RE revealed posterior staphyloma. She was diagnosed with OD refractive surprise, pseudophakia, posterior staphyloma, and OS pseudophakia. She underwent IOL exchange surgery on her RE. Post-operatively, the visual acuity of the RE was 7/45 using the Snellen chart. Three months post-op, the BCVA of RE was 10/10. Conclusions: In well-prepared cataract surgery, unexpected refractive outcomes such as a refractive surprise can be prevented. IOL exchange with ciliary sulcus placement technique is a treatment option for refractive surprise associated with posterior capsule rupture, and it has a good outcome.